Smartphone Addiction Inventory (SPAI): Psychometric properties and confirmatory factor analysis. (October 2016) - Pavia, Laura; Cavani, Paola; Di Blasi, Maria; Giordano, Cecilia
Abstract: The Smartphone Addiction Inventory (SPAI) was developed to assess smartphone addiction in Taiwanese university students. The purpose of the current research is to evaluate the factor structure and psychometric properties of the SPAI in Italian university students. A total of 485 university students (29.3% boys) completed the SPAI and the Young's Internet Addiction Test (IAT). The proposed four-factor model of the SPAI-I was tested by computing CFA, and the results of the goodness of fit indices indicated an ambiguous solution. An exploratory-confirmatory cross validation strategy was applied for a better trimming of SPAI-I factorial structure. Results suggested a five-factor solution that explained 53% of the total variance (Time Spent, Compulsivity, Daily Life Interference, Craving, and Sleep Interference). Excellent internal consistency and five factor correlations were reported for the SPAI-I. This five-factor model showed good convergent validity with the Internet Addiction Disorder Test. Considering that evidence shows that overuse of a smartphone can be associated with adverse and problematic effects, the SPAI-I should be useful for determining its potential for the use in future research in Europe and for comparing the evaluation of smartphone overuse of young European people with other international Asiatic studies that have incorporated the SPAI. Highlights: The SPAI was tested using factorial analysis procedures in a large sample. The exploratory factor analysis revealed five factors rather than the original four. The SPAI-I showed satisfactory psychometric properties. The SPAI-I is suitable for measuring smartphone addiction. The SPAI-I may help to promote unified research in the smartphone addiction field.